2011
DOI: 10.1080/14786435.2010.543092
|View full text |Cite
|
Sign up to set email alerts
|

Observation of log-periodic oscillations in the quantum dynamics of electrons on the one-dimensional Fibonacci quasicrystal

Abstract: We revisit the question of quantum dynamics of electrons on the off-diagonal Fibonacci tight-binding model. We find that typical dynamical quantities, such as the probability of an electron to remain in its original position as a function of time, display log-periodic oscillations on top of the leading-order power-law decay. These periodic oscillations with the logarithm of time are similar to the oscillations that are known to exist with the logarithm of temperature in the specific heat of Fibonacci electrons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The exponent should tend to the expected value 1 in the periodic limit when the spectrum becomes continuous (t C. Log-periodic oscillations Abe and Hiramoto (1987) observed that there are oscillations superposed on top of the average power-law behavior of the rms distance dði 0 ; tÞ. These oscillations were studied in more detail by Lifshitz and Even-Dar Mandel (2011). A similar oscillatory behavior is seen for the return probability pð0; tÞ.…”
Section: B Autocorrelation Functionmentioning
confidence: 77%
“…The exponent should tend to the expected value 1 in the periodic limit when the spectrum becomes continuous (t C. Log-periodic oscillations Abe and Hiramoto (1987) observed that there are oscillations superposed on top of the average power-law behavior of the rms distance dði 0 ; tÞ. These oscillations were studied in more detail by Lifshitz and Even-Dar Mandel (2011). A similar oscillatory behavior is seen for the return probability pð0; tÞ.…”
Section: B Autocorrelation Functionmentioning
confidence: 77%
“…In recent years also some new properties for one-dimensional quasiperiodic chains were found. These include the step-like behaviour of the wave-packet dynamics of metallic-mean chains reported by us [20] and the discovery of log-time-periodic oscillations of wave packets in the Fibonacci chain [21].…”
Section: Introductionmentioning
confidence: 91%
“…this model have been studied (Kohmoto and Banavar, 1986;Lifshitz and Dar Mandel, 2011) and found to share electronic properties of multifractal structure and log periodic oscillations. For more information on phonon modes in quasicrystals we refer the reader to (Janssen et al, ????…”
Section: A Phonon Modelsmentioning
confidence: 99%
“…The 1D chain can be used as the basis for extensions to arbitrary dimensions d. Taking d = 2, for example, the direct product C n × C n of two Fibonacci approximants aligned along x and y axes forms a 2D lattice of squares and rectangles (Lifshitz, 2002). As can be seen in Fig.…”
Section: B Product Latticesmentioning
confidence: 99%